(untitled) (Research, Society and Development, 2021)
The reduction in bone height in posterior regions of the maxilla is common in edentulous jaws. Patients who wish to undergo rehabilitation with implants need to undergo additional treatments to obtain bone gain in height. Among the most common treatments for vertical gain, lifting the maxillary sinus with filling the cavity with biomaterials and / or autogenous graft is the most reported form in the literature. Studies have shown that the use of a blood clot as a filling material and immediate implant installation enables bone neoformation and osseointegration. This paper aims to report a clinical case of bilateral sinus lift comparing the filling form (autogenous bone vs clot) and to evaluate differential aspects in bone neoformation with immediate implants. The procedure was performed on a 37-year-old male patient with the absence of elements 16 and 26. To fill the left sinus, particulate autogenous bone was used and the blood clot in the right sinus. During 1 year of follow-up, 5 computed tomography scans were performed, which revealed new bone formation in the two maxillary sinuses and the absence of membrane collapse. In the analysis of the variation of density as a function of time and type of treatment, a decrease in bone density was observed after a period of one year in both groups. In cross-sectional analyzes, it was observed that the two treatments have similar measures of density, indicating that the experimental treatment can be as effective as the control treatment. The results are considered positive considering the simplification of the technique used in comparison with that which requires a donor area.